Tibet behind China - Sandra-Lucia Istrate (HyperCultura, 2012)
Abstract Considered by many a hidden country, due to those very few parts of its civilization that tourists are allowed to visit and due to the distortion of its history since the Chinese invasion in 1949, Tibet has, however, managed to maintain its traditional way of life inside the state and in exile. The invaders chose to destroy the natives’ values and impose a new culture, a different religion and civilization they defined as multiculturalism, a notion they tried to prove to the entire world through propaganda. Yet, as this paper will show, the Tibetan-Chinese relationship is characterized instead by a unicultural system trying to eliminate everything national. The first part of the paper will defend Dalai Lama’s image, so as to answer the Chinese charges of corruption and selfinterest. The second part will argue that the current political regime is totalitarian and nationalist instead of democratic and multiculturalist, through a discussion of different manifestations there as well as through a brief comparison with other states under similar or opposed situations.